IDENTIFIKASI BENTUK MIKROPLASTIK DI SUNGAI MARTAPURA (STUDI KASUS: SISI BARAT MUARA KELAYAN) - Fatimah, Anita (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Microplastics are plastics with a size > 5 mm – 1 µm. The existence of microplastics is influenced byhuman activities. Muara Kelayan is an area that is flowed by the Martapura River which has the largestpopulation in Banjarmasin. This study aims to identify forms of microplastics in water and sediments.The sampling method uses purposive sampling and repetition referring to SNI 8995 – 2021. Themicroplastic extraction method in water uses 10% KOH and NaCl, the sediment extraction method usesoven drying at 70°C and NaCl. The form of microplastic is observed using a binocular microscope witha magnification of 40x and Sedgewick Rafter Cell (SRC) as preparat. The mikroplastik identified in waterwas in the form of 93.05% fiber, 4.71% fragments and 2.24% film. The form of mikroplastik in thesediment samples was 63.95% fiber, 30.63% fragment, 5.06% film, and 0.36% pallet.